1997
DOI: 10.1074/jbc.272.3.1891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Amino Acid Attached to Escherichia coli Initiator tRNA on Its Affinity for the Initiation Factor IF2 and on the IF2 Dependence of Its Binding to the Ribosome

Abstract: We show that the nature of the amino acid in the formylaminoacyl-tRNA influences initiation factor (IF) 2 dependence of its ribosome binding and that this IF2 dependence reflects the relative affinity of the formylaminoacyl-tRNA for the initiation factor IF2. We compared the template-dependent ribosome binding activities, in the presence of initiation factors, of wild type and anticodon sequence mutants of Escherichia coli initiator tRNAs that carry formylmethionine (fMet), formylglutamine (fGln), or formylval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 46 publications
(42 reference statements)
3
50
1
Order By: Relevance
“…The nature of the amino acid attached to the tRNA is less important for IF2 binding than is formylation. Hence, IF2 is able to bind to fVal-tRNA and fGln-tRNA but not to the unformylated tRNAs (251). However, moderate overexpression of IF2 leads to translation initiation without formylation of Met-tRNA f Met , and IF2 stimulates the binding of unformylated Met-tRNA f Met to 30S ribosomal subunits in vitro (68,250).…”
Section: Initiator Trnamentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the amino acid attached to the tRNA is less important for IF2 binding than is formylation. Hence, IF2 is able to bind to fVal-tRNA and fGln-tRNA but not to the unformylated tRNAs (251). However, moderate overexpression of IF2 leads to translation initiation without formylation of Met-tRNA f Met , and IF2 stimulates the binding of unformylated Met-tRNA f Met to 30S ribosomal subunits in vitro (68,250).…”
Section: Initiator Trnamentioning
confidence: 99%
“…Original proposals suggested that IF2 carries fMet-tRNA f Met to the ribosome by analogy to EF1A for aminoacyl-tRNAs and eIF2 for Met-tRNA i Met (reviewed in reference 94). A specific binary complex can be formed between fMet-tRNA f Met and IF2 in vitro, but the interaction is weak, with a K d of 1.8 M, and the complex dissociates readily in the presence of magnesium ions (113,118,119,167,251). Most evidence suggests that IF2 performs its interactions with fMet-tRNA f Met on the 30S ribosomal subunit (251).…”
Section: Initiator Trnamentioning
confidence: 99%
“…Total tRNA was isolated from CV1 cells infected with SV40 carrying the G34C36 mutant initiator tRNA gene as described previously (10). Aminoacylation of tRNA with valine was performed using an E. coli S-100 extract enriched for ValRS as described by Wu and RajBhandary (57).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro evidence suggests that the 30S subunit binds to mRNA or to fMet-tRNA in a random order and in rapid equilibrium to form a 30S-mRNAfMet-tRNA ternary complex, followed by a rate-limiting 'rearrangement' to form the 30S 'initiation complex' (Gualerzi and Pon, 1990). However, in vivo evidence suggests that, at least for some mRNAs, the 30S subunit binds first to the fMet-tRNA, delivered by IF2, and then binds the mRNA Wu and RajBhandary, 1997). The SD sequence, within the untranslated leader, provides for an increase in the K a of 30S-mRNA binary complex formation, but does not influence mechanistically the formation of the 'initiation complex', the rate of initiation, or the establishment of reading frame (Gualerzi and Pon, 1990).…”
Section: Introductionmentioning
confidence: 99%